Export Determinants of RCEP Negotiating Countries: Does REER Matter? - Susilo, Ignatia Bintang Filia Dei; Ramadhan, Rifky Wahyu (WELFARE Jurnal Ilmu Ekonomi, 2023)
With the use of panel data analysis, this study seeks to determine how the Real Effective Exchange Rate (REER) affects the overall exports from the ASEAN-5 nations (Indonesia, Singapore, Malaysia, Thailand, and the Philippines) as well as several neighboring nations (Australia, India, Japan, South Korea, New Zealand, and China). An increase in a country's REER indicates a weakening of the country's trade competitiveness, assuming the other variables remain (ceteris paribus). Based on the results of the study, it was found that the effect of REER was different for ASEAN-5 and non-ASEAN and did not significantly affect the total exports of the 11 countries. The REER coefficient is positive for non-ASEAN countries and the value is higher for high-income countries. The REER coefficient is negative for ASEAN-5 countries but not significant. The negative value is more significant for middle-income countries. The effect of REER on total exports can depend on the type of commodity traded in a country (using natural resources that are abundant in the country or not). Export products that rely on imported raw materials cause when depreciation occurs, the price of raw materials becomes more expensive, increases the price of the final product, and also decreases the terms of trade of related products.Dengan menggunakan analisis data panel, penelitian ini bertujuan untuk mengetahui bagaimana Real Effective Exchange Rate (REER) mempengaruhi keseluruhan ekspor dari negara-negara ASEAN-5 (Indonesia, Singapura, Malaysia, Thailand, dan Filipina) serta beberapa negara tetangga (Australia, India, Jepang, Korea Selatan, Selandia Baru, dan Tiongkok). Peningkatan REER suatu negara mengindikasikan melemahnya daya saing perdagangan negara tersebut, dengan asumsi variabel lain tetap (ceteris paribus). Berdasarkan hasil penelitian diketahui bahwa pengaruh REER berbeda untuk ASEAN-5 dan non-ASEAN dan tidak berpengaruh signifikan terhadap total ekspor 11 negara tersebut. Koefisien REER positif untuk negara non-ASEAN dan nilainya lebih tinggi untuk negara berpenghasilan tinggi. Koefisien REER negatif untuk negara-negara ASEAN-5 tetapi tidak signifikan. Nilai negatifnya lebih besar dan signifikan untuk negara berpenghasilan menengah. Pengaruh REER terhadap total ekspor dapat bergantung pada jenis komoditas yang diperdagangkan di suatu negara (menggunakan sumber daya alam yang melimpah di negara tersebut atau tidak). Produksi barang ekspor dengan bahan baku impor menyebabkan ketika terjadi depresiasi, harga bahan baku menjadi lebih mahal, menaikkan harga produk akhir, sehingga menurunkan terms of trade produk terkait.